1998
DOI: 10.1007/s004010050762
|View full text |Cite
|
Sign up to set email alerts
|

Argyrophilic tau-positive twisted and non-twisted tubules in astrocytic processes in brains of Alzheimer-type dementia: an electron microscopical study

Abstract: This report concerns pathological astrocytic tubular structures (astrocytic tubules, As-Tbs) that coexist with glial filaments in astrocytic processes in brains with presenile-onset Alzheimer-type dementia. The formation of As-Tbs appears to be related to the duration of disease and the intensity of Alzheimer histopathology. In three cases in which the disease was of extremely long duration, As-Tbs were found in the frontal and temporal neocortices, the temporal pole and the hippocampus using electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Alternatively CAA may disrupt perivascular drainage via perturbations in normal arteriolar pulsation (Hawkes et al, 2014;Kress et al, 2014). It is also possible that the presence of hyper-phosphorylated tau has direct deleterious consequences for perivascular astrocytes, for example by directly disrupting their microtubular structure, or altering the expression or localisation of membrane channels (for example, aquaporin 4) that change normal interstitial fluid dynamics, with the eventual outcome of an enlarged perivascular space (Arima et al, 1998;Thrane et al, 2014;Iqbal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively CAA may disrupt perivascular drainage via perturbations in normal arteriolar pulsation (Hawkes et al, 2014;Kress et al, 2014). It is also possible that the presence of hyper-phosphorylated tau has direct deleterious consequences for perivascular astrocytes, for example by directly disrupting their microtubular structure, or altering the expression or localisation of membrane channels (for example, aquaporin 4) that change normal interstitial fluid dynamics, with the eventual outcome of an enlarged perivascular space (Arima et al, 1998;Thrane et al, 2014;Iqbal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In AD, twisted and non-twisted tubules in astrocytic processes were demonstrated to closely resemble twisted and straight tubules in neurons. 15,16 Coiled bodies and argyrophilic threads were demonstrated to be comprised of abnormal tubules, 13-15 nm smooth tubules with fuzzy outer contours in PSP, 17 and 15-20 nm tubules with occasional constrictions in CBD, 18 both of which resemble tautubules in NFT.…”
Section: Tau Filaments In Astrocytes and Oligodendrocytesmentioning
confidence: 97%
“…These studies, however, were limited to evaluation of the MTL and did not take account of cortical and subcortical tau astrogliopathy. Few studies reported tau immunopositivity in glial cells in AD cases with prolonged duration of the disease [5, 48, 68]. Finally, a report on NFT-dementia mentioned the presence of astrocytic tau pathology in white matter and cortex [31].…”
Section: Overview Of Astrocytic Tau Pathologies In the Aging Brainmentioning
confidence: 99%
“…The introduction of the Gallyas silver stain and particularly diagnostic tau immunohistochemistry led to the identification of astroglial tau pathology in the aging brain in people with or without AD-related changes, cognitive decline or movement disorders [5, 7, 11, 21, 25, 31, 3436, 38, 46, 57]. There have been attempts to classify these tau astrogliopathies [34], but there is lack of consensus as to how best to describe and categorize them.…”
Section: Introductionmentioning
confidence: 99%